2016
DOI: 10.1093/femsec/fiw024
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal fungal communities respond to experimental elevation of soil pH and P availability in temperate hardwood forests

Abstract: Many forests are affected by chronic acid deposition, which can lower soil pH and limit the availability of nutrients such as phosphorus (P), but the response of mycorrhizal fungi to changes in soil pH and P availability and how this affects tree acquisition of nutrients is not well understood. Here, we describe an ecosystem-level manipulation in 72 plots, which increased pH and/or P availability across six forests in Ohio, USA. Two years after treatment initiation, mycorrhizal fungi on roots were examined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 81 publications
5
54
2
Order By: Relevance
“…In a previous short-term study in Stebbins Gulch, we also found that communities within the same season differed between sampling years, suggesting that annual environmental conditions have large effects on community structure even within the same season (Burke 2015). These findings are in agreement with other studies finding that soil pH (Kluber et al 2012, Carrino-Kyker et al 2016), N (Lilleskov et al 2002, Courty et al 2008, Leff et al 2015, P (Burke et al 2009, Kluber et al 2012, Coince et al 2013, and soil C:N (Wubet et al 2012, Coince et al 2013 can affect fungal communities; soil chemical changes may also explain vertical variation in communities with soil profile depth (Rosling et al 2003, Lindahl et al 2007, Courty et al 2008, Shahin et al 2013.…”
Section: Nmdssupporting
confidence: 92%
See 1 more Smart Citation
“…In a previous short-term study in Stebbins Gulch, we also found that communities within the same season differed between sampling years, suggesting that annual environmental conditions have large effects on community structure even within the same season (Burke 2015). These findings are in agreement with other studies finding that soil pH (Kluber et al 2012, Carrino-Kyker et al 2016), N (Lilleskov et al 2002, Courty et al 2008, Leff et al 2015, P (Burke et al 2009, Kluber et al 2012, Coince et al 2013, and soil C:N (Wubet et al 2012, Coince et al 2013 can affect fungal communities; soil chemical changes may also explain vertical variation in communities with soil profile depth (Rosling et al 2003, Lindahl et al 2007, Courty et al 2008, Shahin et al 2013.…”
Section: Nmdssupporting
confidence: 92%
“…Taxa names are displayed for some significant indicator taxa; only OTUs that could be confidently assigned to order or better are named here. This is less than an estimate of fungal diversity that we noted for other hardwood forests in Ohio (3174 OTUs;Carrino-Kyker et al 2016); however, the current study focused on one forest, while our previous work was comprised of soil samples collected from six different forests. Our nextgeneration sequencing approach, and the environmental data we collected at a fine scale, allowed us to consider whether fungal responses to environmental factors could be conserved, potentially leading to predictability of environmental responses within clades (Martiny et al 2015).…”
Section: Nmdsmentioning
confidence: 69%
“…We demonstrate that in highly acidic soil more plant C is lost to the external ecosystem carbon cycle than in less acidic soils. Previous studies have suggested a decrease in mycorrhizal fungal colonization of roots in highly acidic soils (St Clair & Lynch, ; Carrino‐Kyker et al , ; Leberecht et al , ). If this applies also to our study, reduced sink strength of mycorrhizal fungi for plant photosynthates in acidic soil may have increased root exudation rates – a hypothesis that has to be tested in future studies.…”
Section: Resultsmentioning
confidence: 95%
“…The specific mechanism(s) driving this response is beyond the scope of this study. However, there are several possible processes that could generate this pattern: Soil Mn, Ca, and Mg availability is linked to soil pH, so that the response of ECM communities to these cations signals the effects of soil pH [77]. Plant morphology also varies with soil fertility meaning that major differences in root traits (root length, fine root density) could indirectly alter the ECM community [78].…”
Section: Discussionmentioning
confidence: 99%